GROWTH, STRUCTURAL AND OPTICAL STUDIES ON PURE AND L-HISTIDINE DOPED SINGLE CRYSTALS OF COPPER SULPHATE - G.P. Bhavanee1, V. Syamala2, K. Umamaheswar3, K.A. Emmanuel4, J. Sai chandra5; K.V.L.N Murthy6 (Chelonian Research Foundation, 2023)
Single crystals of pure and L-Histidine doped copper sulphate penta hydrate (CuSO4. 5H2O) were grown by slow evaporation method at room temperature. The grown crystals were carried out by Powder X-ray diffraction analysis to find out the crystalline nature. The different modes of vibration present in the pure and L-Histidine doped CuSO4 crystals were identified by FITR spectra. The wide optical transparency in the entire visible region was shown by UV-Vis-spectral analysis. Keywords: Crystal Growth, XRD, FTIR, UV-Visible